2015
DOI: 10.1242/dev.117507
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest migration is driven by a few trailblazer cells with a unique molecular signature narrowly confined to the invasive front

Abstract: Neural crest (NC) cell migration is crucial to the formation of peripheral tissues during vertebrate development. However, how NC cells respond to different microenvironments to maintain persistence of direction and cohesion in multicellular streams remains unclear. To address this, we profiled eight subregions of a typical cranial NC cell migratory stream. Hierarchical clustering showed significant differences in the expression profiles of the lead three subregions compared with newly emerged cells. Multiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
130
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 47 publications
12
130
0
Order By: Relevance
“…Second, using the example of SOX10, ITGB5, and NBL1 we quantified their regional expression differences within a typical cranial neural crest cell migratory stream and within single cells. High expression of ITGB5 in lead neural crest cells confirmed our RT-qPCR results (McLennan et al, 2015) and provided confidence that ITGB5 signaling may be important for neural crest cell invasion. Third, spot detection of SOX10, ITGB5, and NBL1 transcripts in HNK1-positive neural crest cells showed most cells express all three genes and detection of spots is not solely dependent on the cell size.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Second, using the example of SOX10, ITGB5, and NBL1 we quantified their regional expression differences within a typical cranial neural crest cell migratory stream and within single cells. High expression of ITGB5 in lead neural crest cells confirmed our RT-qPCR results (McLennan et al, 2015) and provided confidence that ITGB5 signaling may be important for neural crest cell invasion. Third, spot detection of SOX10, ITGB5, and NBL1 transcripts in HNK1-positive neural crest cells showed most cells express all three genes and detection of spots is not solely dependent on the cell size.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, our single cell RT-qPCR analysis revealed a set of 16 out of 96 genes highly expressed and consistent during migration in cells restricted to the invasive front (McLennan et al, 2015). This heterogeneity of expression is driven by microenvironmental signals as cells travel through different microenvironments (McLennan et al, 2015). In order to better understand the molecular underpinnings of this neural crest cell invasion signature and gene expression heterogeneity within a typical migratory stream, it was clear we needed to develop a rapid means to visualize multiple genes within individual migrating neural crest cells in the same embryo as cells traveled to deep peripheral locations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The fact that amplification polymers carry up to hundreds of fluorophores (Choi et al, 2014) makes it possible to achieve high signal-to-background even when autofluorescence is high [e.g. in whole-mount vertebrate embryos (Choi et al, 2014;McLennan et al, 2015;Huss et al, 2015), in thick mouse brain sections (Sylwestrak et al, 2016) or in bacteria contained within environmental samples or other organisms (Rosenthal et al, 2013;Yamaguchi et al, 2015;Nikolakakis et al, 2015)]. The resulting HCR signal is stable for at least 1 week in zebrafish embryos stored in solution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a unique molecular signature was found to be consistently expressed throughout migration in a subset of NCCs at the leading edge of the migrating stream. When this molecular signature is perturbed in cranial NCCs, migration distances and patterns are disrupted (McLennan et al, 2015). However, subsequent work has shown that physical ablation of NCCs at the leading edge does not appear to impact cranial NC migration (Richardson et al, 2016).…”
Section: Migratory Mechanisms and Communicationmentioning
confidence: 99%